(Ir)rationalités In/Ex-térieures - Koutsomichalis, Marinos (My University, 2026)
Algorithmic network-art audiovisual composition/performance. Individuals live-stream audio/video to a server in Germany, wherein bespoke software process/manipulates that in real-time (also taking into account textual instructions sent by the composer and selected individuals) to compose a synthesised audio/visual stream to be further streamed for performance. Presented at: http://apo33.org/index.php/2021/02/16/audioblast-festival-9/